Theoretical Analysis of a Two-stage Sagnac loop filter using Jones Matrices - N. A. B. Ahmad; S. H. Dahlan; N. A. Cholan (Institute of Advanced Engineering and Science, 2017)
In this work, a theoretical analysis of a Sagnac loop filter (SLF) with two-stage polarization maintaining fibers (PMFs) and polarization controllers (PCs) is presented. The transmission function of this two-stage SLF is calculated in detail by using Jones matrix. The calculation is performed in order to investigate the filtering characteristics. The theoretical results show that the wavelength interval is depending on the dynamic settings of the length of the PMFs and the polarization angle of the PCs. By changing the polarization angle of the PCs, a multiple of single, dual or triple wavelength in each channel can be achieved. Based on this study, a flat multiwavelength spectrum can be obtained by adjusting the PMFs and the PCs in the two-stage SLF. This finding significantly contributes to the generation of multiwavelength fiber laser (MWFL) that can be used for many optical applications.